2023
DOI: 10.1177/11795476231171391
|View full text |Cite
|
Sign up to set email alerts
|

Lambl’s Excrescence as an Etiology of Thromboembolism: Case Report and Literature Review

Mohammad Ala’ Alajjuri,
Omar Ala’ Alajjuri,
Firas Raouf Alani

Abstract: Lambl’s excrescence (LE), a rare thin linear fibrous thread of collagen and elastic fibrous tissue originating at closure margins of heart valve leaflets is considered a rare cause of thromboembolism, causing ischemic stroke, transient ischemic attack (TIA), acute coronary syndrome, or peripheral thromboembolism. The gold standard for diagnosing LE is transesophageal echocardiography (TEE). Due to the rarity of the disease and lack of significant research, no guidelines exist about the management of LE. Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…Given that she was not initially treated, it is impossible to know if she would have had three or more cardioembolic events despite therapy. Vitamin K antagonist therapy was considered; however, given a lack of evidence for superiority, it was not pursued as a treatment strategy due to the significant testing burden and potential interactions with other medications and foods [ 11 , 12 ]. The decision was made to manage conservatively with apixaban and aspirin dual therapy with continued close monitoring and defer escalation to procedural intervention unless and until the patient had an additional CVA despite pharmacologic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Given that she was not initially treated, it is impossible to know if she would have had three or more cardioembolic events despite therapy. Vitamin K antagonist therapy was considered; however, given a lack of evidence for superiority, it was not pursued as a treatment strategy due to the significant testing burden and potential interactions with other medications and foods [ 11 , 12 ]. The decision was made to manage conservatively with apixaban and aspirin dual therapy with continued close monitoring and defer escalation to procedural intervention unless and until the patient had an additional CVA despite pharmacologic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…9 Mechanistically, due to valvular wear and tear, LEs form on affected valves and act as a nidus for thrombi to accumulate that embolize centrally and peripherally. Although their definite prevalence in asymptomatic patients is unknown, an increasing number of case reports and observational studies have associated LEs with cerebral embolism, 5-7,10-42 acute coronary syndrome, 43-47 peripheral embolism, 19 myocarditis 48 and fatigue 49 in addition to LEs as incidental findings. 50-53 Here, we conduct a comprehensive literature review of reported cases and observational studies pertaining to embolic events associated with LE.…”
Section: Introductionmentioning
confidence: 99%